2016
DOI: 10.1093/cid/ciw418
|View full text |Cite
|
Sign up to set email alerts
|

Durable Viral Suppression and Transmission Risk Potential Among Persons With Diagnosed HIV Infection: United States, 2012–2013

Abstract: Background To examine durable viral suppression, cumulative viral load (VL) burden, and transmission risk potential among HIV-diagnosed persons in care. Methods Using data from the National HIV Surveillance System from 17 jurisdictions with complete reporting of VL test results, we determined the percentage of persons in HIV care who achieved durable viral suppression (all VL results <200 copies/mL) and examined viremia copy-years and time spent above VL levels that increase the risk of HIV transmission duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
99
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 16 publications
6
99
6
1
Order By: Relevance
“…Using a single VL measurement may also overestimate durable viral suppression [37]. However, our definitions provide a snapshot of the continuum in 2013 that is simple to interpret and communicate to policy makers.…”
Section: Discussionmentioning
confidence: 99%
“…Using a single VL measurement may also overestimate durable viral suppression [37]. However, our definitions provide a snapshot of the continuum in 2013 that is simple to interpret and communicate to policy makers.…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal adherence and high rates of loss to follow-up continue to influence the overall effectiveness of ART. A recent analysis of rates of virological suppression in low- and middle-income settings found that when loss to follow-up was taken into consideration, only around 62% of patients starting ART were virologically suppressed four years after starting ART [17] and in the United States only two-thirds of people in HIV care had durable viral suppression during a two-year period [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that viral suppression among US women tended to be lower than the overall national average and lower than the national target of 90% . However, to our knowledge, US HIV surveillance data have not previously been used to examine rural‐urban differences among women with HIV.…”
mentioning
confidence: 91%